2013
DOI: 10.1002/jhm.2035
|View full text |Cite
|
Sign up to set email alerts
|

Functional improvement in hospitalized older adults is independent of dementia diagnosis: Experience of a specialized delirium management unit

Abstract: BACKGROUND Patients with delirium, especially when superimposed on dementia, are at high risk of functional decline. OBJECTIVE To examine the influence of a multicomponent delirium management program, the geriatric monitoring unit (GMU), on functional progress of delirious older patients and the impact of underlying dementia on functional recovery. DESIGN Prospective cohort study. SETTING The GMU is a specialized 5‐bed unit for the care of delirious older adults within an acute tertiary hospital. PATIENTS Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…Some studies have shown that delirium has an adverse impact on rehabilitation outcomes from both short‐ and long‐term perspectives, and this could impair their rehabilitation potential. In contrast, our results are also consistent with the fact that older patients with dementia recovering from delirium have comparable potential for functional recovery as their cognitively intact counterparts …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Some studies have shown that delirium has an adverse impact on rehabilitation outcomes from both short‐ and long‐term perspectives, and this could impair their rehabilitation potential. In contrast, our results are also consistent with the fact that older patients with dementia recovering from delirium have comparable potential for functional recovery as their cognitively intact counterparts …”
Section: Discussionsupporting
confidence: 90%
“…In contrast, our results are also consistent with the fact that older patients with dementia recovering from delirium have comparable potential for functional recovery as their cognitively intact counterparts. 25,26 The present study had limitations, including a retrospective design and a single-center perspective. A further limitation of the present study was investigating cognition as a dichotomous variable.…”
Section: Previous Diagnosis Of Dementia (D)mentioning
confidence: 93%
“…We published initial data on functional improvement in delirious patients admitted to the GMU, independent of their underlying cognitive status,25 supporting the role of the early mobilization and rehabilitation of older persons admitted for acute delirium regardless of their premorbid cognitive functioning. The benefits of bright light therapy in a multicomponent intervention program on sleep, cognitive, and functional outcomes in GMU patients have also been demonstrated 26.…”
Section: Introductionmentioning
confidence: 78%
“…The short- and intermediate-term functional benefits observed were likely due to 1) the comprehensive, multicomponent delirium management intervention, with the contributions of both nonpharmacological interventions and judicious use of pharmacological agents; 2) prevention of complications as a result of early mobilization, absence of physical restraints, and decreased pharmacologic interventions; 3) improved sleep patterns, with a sleep protocol and evening light therapy;26 and 4) an unbiased approach to rehabilitating persons with delirium regardless of the premorbid dementia status 25. This broad approach is even more translatable to clinical practice in a busy acute care hospital than to the more narrow, carefully selected clinical research population.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings, although very preliminary, suggest that older women with dementia, more so than their male counterparts, may gain resistance to greater delirium severity through efforts that improve physical health and prevent high co-morbidity and resultant frailty. Others have found that by attending to mobilization and rehabilitation, delirium can resolve, including in people with dementia (Bee Gek Tay, Chew Chan, & Sian Chong, 2013). We recommend that future studies of gender differences in delirium predictors include measures of frailty in addition to co-morbidity given recent findings that support a close association between these constructs.…”
Section: Discussionmentioning
confidence: 99%